The Factors that Influence the Loan Repayments of Credit Union Members and Performance Analysis on Credit Union - Rasyidi, Achyar; Firdaus, Muhammad; Sasongko, Hendro (UI Scholars Hub, 2016)
Takera Credit Cooperative has a high level of non-performing loans (NPL) at 6.60 percent with greater emphasis on financial aspects in measuring its performance. The purpose of this study includes: (1) To analyze the factors that influence the loans repayments of the members of Takera Credit Cooperative to decrease NPL below 5 percent, (2) To evaluate the performance of Takera Credit Cooperative based on the Balanced Scorecard approach, (3) To formulate the alternative policy that become priority in improving the management performance of Takera Cooperative Credit. This research paper uses the case study approach on the factors that influence the loans repayments of the members, which is analyzed using logistic regression and descriptive analysis. The performance of Takera Credit Cooperative is analyzed with AHP in weighting scoring criteria on BSC perspective. The results of this study are: (1) Loans is given to the members in the group with a